2009
DOI: 10.1021/om900182z
|View full text |Cite
|
Sign up to set email alerts
|

Silylene- and Germylene-Mediated C−H Activation: Reaction with Alkanes, Ethers, and Amines

Abstract: The reaction of silylene Si[N 2 ( t Bu) 2 C 2 H 2 ] and Ph-X (X ) I, Br) in alkane and ethereal solvents results in the formation of C-H activation product [C 2 H 2 ( t Bu 2 )N 2 ]SiRI and an equivalent of benzene or oxidativeaddition product [C 2 H 2 ( t Bu 2 )N 2 ]SiPhI. The ratio of products obtained is dependent upon substrate and concentration. This class of reaction has been extended for Si[N 2 ( t Bu) 2 C 2 H 2 ] and Ge[CH(SiMe 3 ) 2 ] 2 to alkylamines. The primary kinetic isotope effect has been measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…These investigations reveal that t Bu 2 NHSi and t Bu 2 NHSi H2 react with a variety of chloro‐ or bromocarbons to yield to the monosilanes H , disilanes I or mixtures of both, depending on the halocarbon and the stoichiometric ratio used (Figure 9, top left) [4c,24a] . Holl and co‐workers reacted t Bu 2 NHSi with phenyl iodide to obtain t Bu 2 NHSi(I)(Ph), and subsequent addition of N ‐methyl piperidine led to the isolation of t Bu 2 NHSi(I)(Py Me ) via a C−H activation in ortho ‐position of the piperidine nitrogen atom [24b] . Furthermore, it was shown that two molecules of the benzannulated, CH 2 t Bu substituted silylene ( t BuCH 2 ) 2 NHSi benz insert into the C−Cl (C−Br) bonds of dichloromethane or dibromo methane, respectively, to give the methylene bridged disilane J (Figure 9, bottom left) [29] .…”
Section: Resultsmentioning
confidence: 99%
“…These investigations reveal that t Bu 2 NHSi and t Bu 2 NHSi H2 react with a variety of chloro‐ or bromocarbons to yield to the monosilanes H , disilanes I or mixtures of both, depending on the halocarbon and the stoichiometric ratio used (Figure 9, top left) [4c,24a] . Holl and co‐workers reacted t Bu 2 NHSi with phenyl iodide to obtain t Bu 2 NHSi(I)(Ph), and subsequent addition of N ‐methyl piperidine led to the isolation of t Bu 2 NHSi(I)(Py Me ) via a C−H activation in ortho ‐position of the piperidine nitrogen atom [24b] . Furthermore, it was shown that two molecules of the benzannulated, CH 2 t Bu substituted silylene ( t BuCH 2 ) 2 NHSi benz insert into the C−Cl (C−Br) bonds of dichloromethane or dibromo methane, respectively, to give the methylene bridged disilane J (Figure 9, bottom left) [29] .…”
Section: Resultsmentioning
confidence: 99%
“…That is to say, H 2 O was included in the reaction mixture. It is known that H 2 O is an effective additive to promote the CO 2 fixation reactions with tetraalkylammonium iodide catalysts. , To clarify the effect of H 2 O in the present reaction system using a triethylamine hydroiodide catalyst, we prepared a dry triethylamine hydroiodide catalyst, and the catalytic ability was compared with an in situ -generated catalyst including water (Scheme ). The pre-prepared dry triethylamine hydroiodide catalyst exhibited basically the same catalytic activity with the in situ -generated catalyst including water, and product 2a was obtained in high yield (94% yield).…”
Section: Resultsmentioning
confidence: 99%
“…IR spectroscopy for salts [ 1 -H – ]­[M + ] showed distinct stretching modes of the Si–H bonds at 2176 cm –1 [K+] or 2243 cm –1 [PPh 4 + ]. Such values are much higher compared to other hydridosilicates (1550–1970 cm –1 ), ,, but rather match with those of Si–H bonds in neutral silanes or aminosilanes (2100–2200 cm –1 ). ,, The IR-spectra thus indicate a remarkably strong Si–H bond in [ 1 -H – ].…”
mentioning
confidence: 61%